2019
DOI: 10.1002/jcp.28086
|View full text |Cite
|
Sign up to set email alerts
|

Increased autocrine interleukin‐6 production is significantly associated with worse clinical outcome in patients with chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) remains incurable with current standard therapy. We have previously reported that an increased expression of interleukin‐6 (IL‐6) receptor CD126 leads to resistance of CLL cells to chemotherapy and worse prognosis for patients with CLL. In this study, we determine whether autocrine IL‐6 production by CLL B cells is associated with poor clinical outcome and explore IL‐6‐mediated survival mechanism in primary CLL cells. Our results demonstrate that higher levels of autocrine IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Besides, some other serum markers have also been suggested in recent years. The measurement of autocrine interleukin-6 (IL-6) could be a useful approach to predict clinical outcomes [25]. Higher serum copper level predicts a shorter time to start treatment and poor response to treatment.…”
Section: Serum Markersmentioning
confidence: 99%
“…Besides, some other serum markers have also been suggested in recent years. The measurement of autocrine interleukin-6 (IL-6) could be a useful approach to predict clinical outcomes [25]. Higher serum copper level predicts a shorter time to start treatment and poor response to treatment.…”
Section: Serum Markersmentioning
confidence: 99%
“…IL-6 could ameliorate B-CLL cells' survival by activating STAT3 and NK-kB. The blockage of IL-6 or its receptor could alleviate the problem of B-CLL resistance to the treatment [36].…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 99%
“…IL-6 is known to activate both STAT3 and NF-κB in primary chronic lymphocytic leukemia (CLL) cells. The IL-6 production by CLL B-cells is associated with worse clinical outcome for patients with CLL [ 40 ]. Regarding the connection between the cytotoxicity of DOX and IL-6 production, it was found that IL-6 was significantly up-regulated in DOX-treated tissues and cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%